PENGARUH E- PROCUREMENT TERHADAP KINERJAPENGADAAN BARANG DAN JASA DAN DAMPAKNYA TERHADAP PENCEGAHAN FRAUD (Studi Kasus pada Biro Pengadaan Barang dan Jasa Sekda Lampung) (Fakultas Ekonomi dan Bisnis Universitas Faletehan, 2023)
Fraud is the most avoided thing in every financial statement audit activity. To avoid the risk of fraud in line with advances in technology, electronic systems are used. This study aims to analyze the effect of the application of Electronic (E) - Procurement on the performance of goods and services procurement and its impact on fraud prevention. This research was conducted at the office of the Bureau of Procurement of Goods and Services of the Regional Secretariat of Lampung Province. The method used in this research is quantitative and qualitative, the number of samples in the study is 30 people. The data analysis tool used is multiple regression analysis and path analysis. From the results of the calculations and discussion, it is found that E-Procurement has an effect on the Performance of the Procurement of Goods and Services, E-Procurement has an effect on Froud, Performance of the Procurement of Goods and Services has an effect on Froud. R Square Model 1 earned 90 percent, R Square Model 2 earned 82.2 percent and R Combined 98.2 percent. Shows that E - Procurement has an effect on the Performance of Procurement of Goods and Froud. Keywords : E - Procurement, Goods and Services Procurement Performance, Froud